Perancangan Infografis Interaktif 2D Sebagai Media Informasi Krs Online Bagi Mahasiswa Baru Perguruan Tinggi Asia Malang - brenda dessiyani ismanto; Tengky Triono Bagus (Jurnal Desain Komunikasi Visual Asia, 2018)
In early 2016 Asia University decided to use a new system in the process of drafting the KRS namely an online study plan card. The use of Online KRS system has few constraints because the new system is less socialization of its use so there are still many students who have not understood with the flow of filling Online KRS. Due to obstacles in the flow of filling Online KRS then selected an interactive infographic media to provide understanding and socialization of Online KRS to the students, especially new students who are just undergoing college. Interactive infographic media is created by combining images, text, video, audio and 2-dimensional animation. In this media there are 3 menus: the menu about contains a brief summary of the application contents and a glance of Asia, KRS flow contains the process of filling Online KRS, and author's profile contains about the data of this media maker. In this media there are also exit button, maximaze button, picture button in KRS path to KRS flow description page and next back button. The colors used in this medium are blue, orange, black and white served younger. While the text used is Arial font, Arial Black, Arial Rounded MT Bold, and Arial Narrow. Through this interactive infographic media, the students especially the new students who just undergo a period of unfamiliar and confused college can understand how the flow of filling Online KRS is still being run by Asia Malang. Based on the result of questionnaire of interactive infographic media testing on 60 people, it can be concluded with the interactive infographic media 32% of students were very understanding about the flow of filling Online KRS. 68% of respondents agreed and suitable use of this media as a medium of information flow process filling Online KRS.